Polygamy in Musdah Mulia's View and Its Relevance to Marriage Law in Indonesia - Mardliyati, Saadah; Shesa, Laras (AJIS: Academic Journal of Islamic Studies, 2023)
The pros and cons of polygamy in Indonesia are still an interesting discussion. This discussion becomes increasingly fierce when the facts around us present polygamists who use religious teachings as an excuse for polygamy. Even though polygamy is a personal choice because the essence of Islamic teachings adheres to a monogamous marriage system. Therefore Prof. Dr. Siti Musdah Mulia through her book "Islam Sues Polygamy (Islam Menggugat Poligami)" tries to put this understanding back into perspective, by analyzing 114 verses of the Koran about marriage which concludes that it rejects and even forbids polygamy. The question that arises in this research is: What is the relevance of Musdah Mulia's thoughts on the Marriage Law in Indonesia? This research, which is literature research, is qualitative with a gender analysis approach, complemented by an analytical description of Musdah's thoughts, concluding that the basic principle of Islamic marriage according to Musdah Mulia is monogamy, not polygamy. Musdah also concluded that it was necessary to revise Marriage Law Number 1 of 1974 because it was at odds with the essence of Islam, rahmatan lil alamin.